The relationship between entrepreneurial leadership an organizational innovation among small and medium-sized enterprise entrepreneurs in China: a conceptual framework - Muhamad Nasharudin, Nurfazreen Aina; Rui, Zhao (Macrothink Institute, Inc., 2024)
This study draws on a broad spectrum of research to investigate the theoretical underpinnings of entrepreneurial leadership, highlighting the leader’s vision, creativity, and proactive stance toward identifying and exploiting opportunities. The aim of this research is to examine the factors that influence entrepreneurial leadership and its beneficial impacts. This study will specifically examine how entrepreneurial passion and learning capability influence entrepreneurial leadership, as well as how entrepreneurial leadership contributes to organizational innovation. In addition, it is essential to investigate how strategic flexibility, job crafting, and psychosocial safety climate moderate the influence of entrepreneurial leadership on organizational innovation.